2020
DOI: 10.1101/2020.01.10.901843
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Physiological Characterization in Controlled Bioreactors Reveals a Novel Survival Strategy forDebaryomyces hanseniiat High Salinity and Confirms its Halophilic Behavior

Abstract: 4Debaryomyces hansenii is traditionally described as a halotolerant non-conventional yeast, being 1 5

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Additionally, Gustafsson and Norkrans in 1976 [93] and Adler et al in 1985 [94], described the role of glycerol production and accumulation as a compatible solute in response to high extracellular osmolarity. More recent work on the characterization of D. hansenii in controlled bioreactors, revealed that high salt concentrations are necessary for optimal cell performance in this yeast, especially sodium salts [41]. This confirmed that D. hansenii is halophilic rather than simply halotolerant as previously hypothesized.…”
Section: Use Of Non-pure Water: Debaryomyces Hanseniisupporting
confidence: 81%
See 3 more Smart Citations
“…Additionally, Gustafsson and Norkrans in 1976 [93] and Adler et al in 1985 [94], described the role of glycerol production and accumulation as a compatible solute in response to high extracellular osmolarity. More recent work on the characterization of D. hansenii in controlled bioreactors, revealed that high salt concentrations are necessary for optimal cell performance in this yeast, especially sodium salts [41]. This confirmed that D. hansenii is halophilic rather than simply halotolerant as previously hypothesized.…”
Section: Use Of Non-pure Water: Debaryomyces Hanseniisupporting
confidence: 81%
“…Saline water may not be suitable for the prior biomass pretreatment and enzymatic hydrolysis steps, which are sensitive to salinity deviations [40]. Despite this, its use in the fermentation step would reduce the overall freshwater demand of the process and hence production costs [41].…”
Section: Water Demandmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated that D. hansenii metabolism is enhanced when moderate‐high concentrations of salt (1 M) are found in the media, even though it can tolerate up to 4 M of salt (Breuer & Harms, 2006). Recently, Navarrete, Frost, et al (2021) performed a physiological characterization of D. hansenii in controlled bioreactors testing different salt concentrations (either NaCl or KCl) and assessing cell performance. Moreover, they described a novel survival strategy of this yeast in high salinity environments: when the salt concentration increases from 1 M (optimal for D. hansenii ) to 2 M or more, the yeast changes its metabolism from growing as fast as possible and limiting the nutrients for the competitors, to grow as much as possible and overpopulate the area (Navarrete, Frost, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%